An interesting case of polymelia (throracomelia and pelvomelia): lamb with seven legs - Hüseyin Karadağ; Yusuf Gül; H. Hüseyin Dönmez (Eurasian Journal of Veterinary Sciences)
In this article, a case of polymelia was examined wich observed in a Akkaraman lamb. The lamb had three extra congenital developed legs. One of the extra legs was joined to the presternal region and two of them to the pubic region. On the other hand, it was established that there was a third ren stucked on the cecum. In histobgical observation, it was seen that this ren consisted of two united rens.